EFFECT OF CASHLESS POLICY ON NIGERIA’S ECONOMIC GROWTH - Nasamu Gambo; Danjuma Tsintop Ussaini; Jonathan Peter Ozah (Malete Journal of Accounting and Finance)
This study examined the impact of cashless policy on the economic growth of Nigeria for the period of 2011 - 2018. Data was collected from secondary sources through annual reports obtained from Central Bank of Nigeria Statistical Bulletins. The impact of cashless policy was proxied by Automated Teller Machine (ATM), Point of Sale (POS), and Internet Banking (WEB), while economic growth was proxied by Gross Domestic Product (GDP). Multiple regressions were applied to determine the impact of the policy on the GDP using the ATM, POS and the WEB. The study revealed that ATM has a positive effect on GDP. On the other hand, the regression results also show that POS and WEB had a negative effect on GDP. Based on the findings of the study, it is therefore recommended that awareness should be created on the benefits derivable from cashless policy to stimulate improvement of business activities, thereby enhancing economic growth.